2000
DOI: 10.1016/s0022-5347(05)67916-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of 1,930 Patients With Hematuria to Evaluate Current Diagnostic Practice

Abstract: Our findings suggest that cystoscopy cannot be safely avoided even in younger patients with microscopic hematuria. Only a combination of ultrasound and IVP detected all upper tract tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
219
3
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(245 citation statements)
references
References 20 publications
15
219
3
8
Order By: Relevance
“…In gynecologic section, it was demonstrated that hematuria can be used as a screening test to detect urinary bladder mucosal infiltration of cervical cancer (Chuttiangtum et al, 2012). It has been reported that Urological cancer is found in approximately 5% of the patients presenting with microscopic hematuria, and in around 20% of the patients with gross hematuria (Khadra et al, 2000;Cohen and Brown, 2003). Therefore, screening for bladder cancer may have different performance characteristics in selected high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gynecologic section, it was demonstrated that hematuria can be used as a screening test to detect urinary bladder mucosal infiltration of cervical cancer (Chuttiangtum et al, 2012). It has been reported that Urological cancer is found in approximately 5% of the patients presenting with microscopic hematuria, and in around 20% of the patients with gross hematuria (Khadra et al, 2000;Cohen and Brown, 2003). Therefore, screening for bladder cancer may have different performance characteristics in selected high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, little research has been carried out on the investigation of hematuria (Khadra et al, 2000;Lotan et al, 2009;Cha et al, 2012a). Using age, gender, race, smoking history, hematuria, and NMP22 findings, Lotan et al (Lotan et al, 2009) developed a logistic regression model-based nomogram to predict the presence of bladder cancer in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of our 11 patients of newly diagnosed bladder tumours were aged 49 years and above and this is consistent with review of literature where most bladder tumours have peak incidences at age 50 years and above. However, Khadra et al (2001) have shown that patients below age 40 with microscopic haematuria can still present as bladder tumour.…”
Section: 2515 Assessment and Clinical Significance Of Haematuria In mentioning
confidence: 99%
“…1 Hematuria is often the first sign of bladder cancer, portending malignancy 2.3-25.8 % of the time, depending on the cohort evaluated (population vs. referral), severity of hematuria, and patient-level risk factors such as age, gender, and smoking status. [2][3][4][5][6] The evaluation recommended by the American Urological Association for microscopic hematuria includes cystoscopy and upper tract imaging for those without an obvious benign etiology. 7,8 Population-based studies suggest that the minority of those with hematuria are evaluated (9-36 %), 9,10 a finding that persists even in those at high risk for malignancy.…”
Section: Introductionmentioning
confidence: 99%